Competitive performance correlates of mental toughness in tennis: A preliminary analysis - Cowden, R. G. (Perceptual and Motor Skills, 2016)
This study investigated relationships between mental toughness and measures of competitive performance in tennis. Forty-three male (N = 25) and female (N= 18) players (M age = 13.6 years, SD = 2.4) completed the mental toughness inventory, and the point-by-point outcomes recorded during a competitive tennis match (singles) were used to generate performance indices for each athlete. The results indicated that mental toughness was associated with several, but not all, macro, micro, and critical moment performance indices. The findings suggest mental toughness may contribute to successful performance during tennis competition, although the importance of the construct appears to depend depend on specific match situations. Future mental toughness research should consider a range of factors related to sport performance, including athletes' and opponents' physical, technical, and tactical abilities. ABSTRACT FROM AUTHOR